Participatory Research Emergent Recommendations for Researchers and Academic Institutions: A Rapid Scoping Review - Benjamin D Scher; Juliet Scott-Barrett; Matthew Hickman; Benjamin W Chrisinger (Journal of Participatory Research Methods)
In recent years, a range of academic disciplines have emphasized the potential benefits of prioritizing meaningful engagement with individuals and communities who have lived and have living experience with the topics, phenomena and problems researchers seek to study. In March 2022, we were asked to produce a paper to inform a university workshop and training materials to help students and faculty engage with participatory methods. In turn, we conducted a rapid scoping review of reviews to document key recommendations relating to methodology, logistics and ethics within the various modes of participatory research. Searches were conducted in Web of Science, SCOPUS, ProQuest, Pub Med, OVID (including Medline, PschyInfo/EMBASE, APAPsych) to identify published academic reviews (e.g., systematic, scoping, literature reviews and evidence gap maps), for best practices relating to participatory research. This approach drew out aggregated best practices and lessons learned across many primary studies and increased the speed of the review. From 276 studies imported for screening, 43 full-text studies were assessed for eligibility and 28 were deemed relevant for full inclusion. Results are presented as: 1) participatory research recommendations for researchers; and 2) participatory research recommendations for academic institutions. Three sub-themes emerged within the context of suggestions for researchers engaging with participatory methods: 1) early-stage considerations for study design and planning; 2) conducting the research; and 3) dissemination and knowledge exchange. This rapid scoping review highlights key recommendations for researchers interested in using participatory approaches in their own research, and for academic and institutional stakeholders who aim to support these practices.